(untitled) (El Hilo de la Fabula, 2024)
This paper aims to analyse the representations of migration and otherness in two films of contemporary Argentine cinema: El cielito (2004) by María Victoria Menis and Bolivia (2001) by Adrián Caetano. The aim is to understand how these filmic narratives construct social imaginaries around migration in the context of globalization. The study is based on three main theoretical assumptions: firstly, film as a semiotic-cultural object that reflects on the social and cultural changes of the time. Secondly social representations understood as social constructions that are elaborated from the interaction with the environment and that influence the perception of reality. Finally, the relationship between migration and globalisation is analysed, and how this phenomenon impacts on identities and social spaces. A semiotic analysis of both films is carried out, using as analytical tools the categories of isotopy (the construction of meaning through the repetition of elements and significant relationships) and attending to filmic grammar (narrative and visual elements that configure the filmic discourse). The analysis of the films allows us to identify the following representations of migration and otherness: the migrant as a foreigner is an individual who is out of place, facing difficulties in adapting to the new society, otherness as a threat, that is, as something dangerous or conflictive that generates fear and uncertainty, and spaces of exclusion because migrants in these films are relegated to marginal spaces within society. The analysed films reflect a negative view of migration and otherness, reinforcing existing stereotypes and prejudices in society. There is a tendency to construct spaces of exclusion for migrants, which hinders their social integration. However, at the limit where the chosen corpus approaches the thematization of migrations in global society, the thematization itself generates an opacity and an interpretation in its apparent crystallisation.